Atomistic mechanism of elastic softening in metallic glass under cyclic loading revealed by molecular dynamics simulations. (January 2016) - Ye, Y.F.; Wang, S.; Fan, J.; Liu, C.T.; Yang, Y.
Abstract: Metallic glasses (MGs) have a great potential for structural applications due to their high strength; however, they soften under cyclic loadings and exhibit low fatigue endurance limits. To understand the softening mechanism, molecular dynamics simulations were carried out to study the Cu50 Zr50 MG within the nominal elastic regime, which clearly show that the quasi-static elastic modulus of the MG softens with either the decreasing cyclic frequency or increasing stress amplitude. Through the extensive analysis of the atomic trajectories, we found the complex elastic softening behavior is related to the activation of string-like liquid-like sites and atomic bond breaking in the cyclically deformed amorphous structure. Our current finding provides a quantitative insight into the atomistic mechanism of damage in MGs under cyclic loadings, also shedding light on the important mechanisms for fatigue damage initiation in amorphous solids. Highlights: Cyclic softening in metallic glass is observed in the nominal elastic regime. Cyclic softening appears to be both stress and rate dependent. Cyclic softening is related to atomic-scale vibration heterogeneity.